Analyzing age-friendly design preferences for urban public park, Kuantan, Pahang / Nor Auni Syafikah Zaharum and Nadiyanti Mat Nayan - Zaharum, Nor Auni Syafikah; Mat Nayan, Nadiyanti (2024)
The intention of this research is to assess and examine age-friendly design concepts for Kuantan, Pahang's urban public parks. The research examines how well existing design techniques promote inclusivity, accessibility, and participation in urban public park areas, with a particular focus on the requirements and preferences of the aging population. With a focus on improving the general well-being and quality of life for elderly’s, the research investigates the integration of age-appropriate amenities, accessible features, and recreational possibilities through a thorough literature review and empirical analysis. In addition, the research looks at how smart technology and creative solutions may be used to enhance the park experience for aging by enabling easy navigation, social interaction, and access to relevant health and wellness data. The research initiative requires to give actionable insights and suggestions to assist the creation of sustainable and comprehensive urban design strategies that address the many and changing demands of Kuantan, Pahang's aging population.